2019
DOI: 10.1001/jamaophthalmol.2018.5527
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception of School-aged Children With Amblyopia and Its Association With Reading Speed and Motor Skills

Abstract: Reading and eye-hand coordination deficits in children with amblyopia may impede their ability to demonstrate their knowledge and skills, compete in sports and physical activities, and interact with peers. Because perceived scholastic, social, and athletic competence are key determinants of self-esteem in school-aged children, these deficits may influence a child's self-perception. OBJECTIVE To determine whether amblyopia is associated with lowered self-perception of competence, appearance, conduct, and global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 39 publications
2
54
0
4
Order By: Relevance
“…Although the best-corrected visual acuity of the amblyopic eye is the main outcome in clinical trials and clinical practice regarding amblyopia, recent studies have suggested that best-corrected visual acuity of the amblyopic eye might not be the main reason for the poor life quality of amblyopes. 44,45 The relationship between temporal synchrony deficits within the eye and between eyes in amblyopia and patients' quality of life will need to be further studied. In addition, accumulating evidence indicates that the poor visual performance of amblyopes in spatial visual processing can be improved by refractive correction, patching, atropine, perceptual learning, and other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although the best-corrected visual acuity of the amblyopic eye is the main outcome in clinical trials and clinical practice regarding amblyopia, recent studies have suggested that best-corrected visual acuity of the amblyopic eye might not be the main reason for the poor life quality of amblyopes. 44,45 The relationship between temporal synchrony deficits within the eye and between eyes in amblyopia and patients' quality of life will need to be further studied. In addition, accumulating evidence indicates that the poor visual performance of amblyopes in spatial visual processing can be improved by refractive correction, patching, atropine, perceptual learning, and other methods.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found that amblyopic children and adults have impaired fine motor skills, such as reaching, grasping, object manipulation, and transferring test answers to a multiple-choice form. [17][18][19][20][21][22][23][24][25] A limited number of studies have also found gross motor impairments in amblyopic adults and children performing tasks designed to assess postural stability and walking, [26][27][28] and such impairments can increase the risk of injury. 29 However, these studies had heterogeneous groups with limited age ranges and small sample sizes, thus making it difficult to ascertain factors associated with motor impairments.…”
mentioning
confidence: 99%
“…Based on the current evidence, amblyopia is mainly caused by uncorrected refractive error, strabismus, cataract and ptosis [4]. There is a plethora of visual function deficits of the amblyopic individual that could affect learning, daily activities and psychological state of affected children [5,6]. Therefore, it is essential to get the best treatment during the critical period to avoid severe consequences later on due to this disorder.…”
Section: Introductionmentioning
confidence: 99%